PENGARUH GAYA MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA DI SMAN 1 CIBAL - Jemalin, Margareta Melisa; Lega, Fransisikus Sales (CREDENDUM: Jurnal Pendidikan Agama, 2023)
This study aims to analyze the effect of teacher teaching style on students' learning motivation. The method used in this study is quantitative descriptive. The research sample was taken as much as 77% of the total number of students at SMAN 1 Cibal in the 2022/2023 academic year, resulting in a total of 31 students as respondents. The results of the data analysis show that there is a significant influence between teacher teaching style and student learning motivation. For example, when the teacher is giving lessons, some students lose concentration to listen to the material and show disinterest in learning. This study is expected to provide an understanding to teachers so that they can develop a teaching style that can motivate students positively, so that students are more enthusiastic and actively participate in learning activities.